Rabies re-emergence after long-term disease freedom (Amur Oblast, Russia) - A. D. Botvinkin; I. D. Zarva; I. V. Meltsоv; S. A. Chupin; E. M. Poleshchuk; N. G. Zinyakov; S. V. Samokhvalov; I. V. Solovey; N. V. Yakovleva; G. N. Sidorov; I. A. Boyko; V. G. Yudin; et al. (Ветеринария сегодня)
Retrospective descriptive epizootological study was conducted in the Amur Oblast (Russian Far East), where a rabies outbreak was reported in 2018. The aim of the study was to analyze probable routes of rabies introduction and features of its spatial and temporal spread in the territory that remained free from this infection from 1972 to 2018. In 2018–2021, altogether 1,416 animals were examined for the infection with the rabies virus. Forty-seven animal rabies cases were confirmed; the proportion of wild animals (Vulpes vulpes, Nyctereutes procyonoides, Canis lupus) amounted to 66%. The first cases were detected within 30 km from the state border with China. Nucleotide sequences of the nucleoprotein gene of three rabies virus isolates were determined and their belonging to the Arctic-like-2 genetic lineage was established. Genetically closest rabies virus isolates have been found in Heilongjiang Province (China, 2011, 2018) and Jewish Autonomous Oblast (Russia, 1980). GIS and open Earth remote sensing data were used to map the rabies cases. After 2018, the epizootic spread within the forest-steppe landscapes of the Zeya-Bureya Plain, where human and animal rabies cases had been earlier reported (until 1972). The front of the epizootic spread in a north-eastern direction at an average speed of 59 (16–302) km during one epizootic cycle. The introduction of the rabies virus was most likely along the Amur River valley from downstream regions of Russia and China that are rabies infected.